Feasibility of 15-Minute Delayed Hepatobiliary Phase Imaging Using a 30 Degree Flip Angle in Gadoxetic Acid-Enhanced MRI in the Detection of the Focal Liver Lesion in Cirrhotic Liver - Teerasamit, Wanwarang; Wongpattaranon, Pimpakarn; Suvannarerg, Voraparee (Asian Medical Journal and Alternative Medicine, 2023)
Introduction: Added hepatobiliary phase images (HBI) of gadoxetic acid-enhanced MRI improve sensitivity for detection of focal liver lesions (FLLs) due to good liver-to-lesion contrast-to-noise ratios (CNRs). The 20-minute delay time is a standard recommendation to obtain appropriate HBI which producing the best liver-to-lesion CNRs. Objectives: To compare the liver-to-lesion CNR, contrast ratio (CR), and the sensitivity of FLL detection of a 15-minute delayed HBI using a 30º flip angle (15min-FA30) in gadoxetic acid-enhanced MRI with those of a standard 20-minute delayed HBI using 25º FA (20min-FA25) in patient with cirrhotic liver. Methods: Seventy FLLs from 62 patients who underwent gadoxetic acid-enhanced MRI with 15minFA30 and 20min-FA25 HBI were enrolled. Liver-to-lesion CNRs and CRs were compared between the two groups. Two radiologists independently reviewed the presence of FLLs using a four-point scale and detection sensitivity was calculated. Results: There was no significant difference in the median CNR of all FLLs on the 15min-FA30 (77.6: IQR; 47.4 - 133.2) and that of the 20min-FA25 (81.5: IQR; 48.2 - 140.0). The mean CR of all FLLs on the 15min-FA30 (0.47 ± 0.16) and 20min-FA25 (0.47 ± 0.17) was no significant difference. There was no significant difference in FLLs detection sensitivity for two readers between 15min-FA30 (91.4% and 97.1%) and 20min-FA25 (92.9% and 97.1%) Conclusions: The CNRs, CRs and lesion detection sensitivity of shorten delayed HBI with high FA in gadoxetic acid-enhanced MRI are comparable with the standard delayed HBI in patient with cirrhotic liver. This result indicates that 15min-FA30 can replace 20min-FA25 that help to reduce the total examination time.